Prediction of optimum roughage to concentrate ratio in sweet sorghum (Sorghum bicolor L. Moench) bagasse based total mixed ration for buffaloes using in vitro gas technique - Seshaiah, Chappidi Venkata; Reddy, Y. Ramana; Rao, S. Jagadeeswara; Srivani, M. (Journal of Advanced Veterinary and Animal Research, 2014)
The in vitro gas technique was used to predict the efficiency of sweet sorghum (Sorghum bicolor L. Moench) bagasse (SSB) based total mixed ration comprising different ratios of roughage and concentrate, with the objective of identifying optimum ratio for feeding buffaloes. Eight rations were prepared with roughage to concentrate ratio of 100:0 to 30:70. Significantly (p<0.01) higher in vitro gas production volume (mL) at 24 h incubation were recorded for the rations with roughage (R) to concentrate (C) ratio of 60R:40C to 30R:70C as compared to other rations. Whereas, in vitro organic matter digestibility (IVOMD) was significantly (p<0.01) higher for the rations 70R:30C to 30R:70C as compared to other rations. Metabolisable energy (ME) and truly digestible organic matter (TDOM) were significantly (p<0.01) higher for the rations 90R:10C to 30R:70C as compared to sole SSB. The rations from 90R:10C to 30R:70C were significantly (p<0.01) higher in partitioning factor (PF), microbial biomass production (MBP) and efficiency of microbial biomass production (EMBP) as compared to sole SSB. However, the PF was not significant among rations 50R:50C, 40R:60C and 30R:70C. Therefore, the present study suggested that SSB can be included in total mixed ration of buffaloes at 50-60% for economic ruminant livestock production. http://dx.doi.org/10.5455/javar.2014.a31